SYNCHRONOUS COMPUTER-SUPPORTED COLLABORATIVE WRITING OF THE PROPOSAL DURING THE PANDEMIC - Asotska-Wierzba, Yuliya (Neofilolog, 2021)
Modern technology has already changed the way we live, but the COVID-19 pandemic has provided us educators with an unprecedented situation in which we are faced with the enormous challenge of teaching online for a long period of time. It is therefore important to analyse various techniques for getting the most out of distance teaching, especially in a synchronous mode. The aim of the study discussed in this article was to analyse students’ attitudes towards collaborative online work undertaken in synchronous mode during the pandemic. Thirty-three first-year BA students studying English Philology participated in this study. Respondents reflected on the process of online, synchronous collaboration via MS Teams by answering an online survey. The results of the study revealed that collaborative learning allows participants to actively participate in an online lesson, interact with others, co-construct a writing task, apply the new language introduced in lessons in a practical task and receive almost instant feedback. Consequently, any sense of isolation the students may feel is reduced and a sense of community is developed. In addition to this, a collaborative task enhances students’ use of academic skills and the development of key competences that can lay the foundation for lifelong learning.